Incidence of thyroid diseases in a tertiary hospital: a retrospective study - Sayanna, Shengulwar; Shankar, Muvva Uday; Ranjith Babu, K. (International Surgery Journal, 2019)
Background: Thyroid gland diseases are common in India, particularly hilly and tribal areas. The incidence of thyroid conditions, exact figure is not available but about 5 lakh cases come for Medical Treatment all over India. To study the prevalence of common thyroid diseases in the Sangareddy district area, which is near Hyderabad, particularly age & sex specific incidence. Methods: This is a retrospective study conducted at the Maheshwara Medical College and Hospital, Chitkul, Sangareddy district of Telangana State. The data was collected from the registers of General Surgery outpatient department, operation theatre, medical record section and cytology, histopathology registers of pathology department. A total number of 64 patients were included in this study who was admitted at this hospital during the period of 2 years, from January 2017 to December 2018. The data was analysed by proper statistical methods. Results: The study had shown that most common conditions in this area are benign diseases. The age group ranges 21-30 years, female are most vulnerable (37.51%). The pathological benign condition most common is nodular goiter 48.43%. Conclusions: The observations in this study made may be useful in future to diagnose the cases and advice regarding prevention of the disease.